Analysis of STEM Literacy in the Pacu Jalur Tradition of SMP Negeri 1 Hulu Kuantan Students - Shilvi Mulia; Zulirfan Zulirfan (Journal of Indonesian Science Teachers, 2023)
The Era of Society 5.0 demands that humans are not only proficient in using technology, but also capable of creating technology. The STEM strategy as contextual education can improve the quality of human resources. Pacu Jalur is a culture tradition from Kuantan Singingi Regency, Riau Province of Indonesia which has existed for long time ago and has survived until now. This survey aims to identify the level of STEM literacy in the Pacu Jalur tradition of SMP Negeri 1 Hulu Kuantan students and to identify differences STEM literacy level based on student’s grade. The instrument has been validated by scientists and cultural experts. A total of 26 questions on the test instrument were tested for reliability so that a KR-20 value of .86 was obtained. All students of SMP Negeri 1 Hulu Kuantan became the population of study, with total sample of 125 respondents. The research was analyzed using descriptive analysis and inferential analysis. In general, the results of the analysis show that STEM literacy in the Pacu Jalur Tradition is still very low with an average total score of 29.81. Meanwhile, based inferential analysis, it was identified that there was no significant difference between grade.